Anti-VEGF therapy of neovascular age-related macular degeneration: from randomized trials to routine clinical practice - R. R. Fayzrakhmanov (Российский офтальмологический журнал)
Antivasoproliferative therapy is a revolutionary trend in the treatment of neovascular age-related macular degeneration (nAMD), as it is aimed at blocking growth factors of the newly formed vessels. Currently, two anti-VEGF drugs are registered for ophthalmological use, and the search for new molecules is only gaining momentum. Studying new approaches to treatment and developing innovative drugs, modern medicine relies on the data from international randomized clinical trials (RCT). The fact that this direction attracts much scientific interest is explained by high reliability of the data obtained with RCTs. However, when analyzing the effectiveness of anti-VEGF therapy in patients with nAMD in routine clinical practice, many ophthalmologists are confronted with discrepancies between the expected morphological and functional results as predicted by RCTs and those obtained in reality. It is thus important to bear in mind that RCTs simply determine how the dynamics of morphofunctional parameters should look like, whilst the ideal result is only achievable through correct implementation of therapeutic strategy in real clinical practice. The results obtained in the practice of any specialist wholly depend on how carefully the prescribed treatment protocols are followed by doctors and patients, how burdensome the treatment is, as well as on the potential of the medication. This literary review offers a comparative analysis of the results achieved by using anti-VEGF drugs (ranibizumab and aflibercept) obtained in key RCTs and in routine clinical treatment of nAMD patients.